Araceae Juss. used as an ornamental in Northeastern Brazil - Rodrigues, Ana Cristina Alves; Andrade , Ivanilza Moreira de; Costa, Creusa Carvalho da; Santos , Seliomar de Sousa Oliveira; Souza, Ruanna Thaimires Brandão (Comunicata Scientiae, 2024)
Araceae Juss. is widely used by the local population for various purposes, including food, mysticism and crafts. The aim of this study was to conduct a survey of Araceae species used in neighborhoods in Floriano, Piauí, and to classify these species based on their origin and habit. The research employed the "Rapport" technique and semi-structured interviews with residents of the of Floriano, Piauí, along with an analysis of the species use value. Nineteen species belonging to thirteen genera were documented, categorized into two main uses: ornamental and mystical. Species such as Aglaonema commutatum Schott, Dieffenbachia seguine Schott, Epipremnum aureum (Linden & André) G.S.Bunting and Zamioculca zamiifolia (Lodd.)Engl. exhibited the highest use value (0.016 each). These species are predominantly cultivated and are of exotic origin, with varying habits including climbing, epiphytic, hemiepiphytic, and herbaceous. Caladium bicolor, Monstera obliqua and Philodendron acutatum are species native to Brazil, found in the Northeast region. However, only while Philodendron acutatum was recorded on the flora of the state. Studies like this contributes to the dissemination of local knowledge and facilitate the exploration of the Araceae flora. Further research is warranted to identify additional use categories and to catalog Araceae species specific to the state, given the limited availability of studies on this plant family in the region.